(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the patient satisfaction after receiving aerosol generating procedures in a dental setting during COVID-19 pandemic. Secondly to investigate the patient’s point of view regarding their experience of dental hospital. Study Design: Mixed method cross sectional descriptive study Place and Duration of Study: This study was conducted at the University Dental Hospital, affiliated with University College of Dentistry, The University of Lahore from 17th Jan, 2022 to 18th Feb, 2022. Materials and Methods: A survey using a self-administered questionnaire was conducted in a tertiary care dental hospital patients who gave consent to participate in the study. Participants expressed their responses in a 5 point Likert scale. SPSS version 24 was used to analyze the results and chi-square test was applied for intergroup comparison. Results: A total of 99 patients participated in the study out of which 48% patients were 18-25 years old, 33% were 26-40 years old, 12% 41-55 years old and 7% were ≥55 years. 56% were female and 44% were male. Most affirming positive resposnes were obtained for body temperature screening at the entry point, professional and caring attitude of doctors and feeling comfortable while visiting dental hopsital. All these statements got more than 50% response rate as strongly agree. Conclusion: It can be concluded that majority of the patients who received aerosol generating procedures from dental clinic were satisfied with the SOPs and the professional attitude of the dentists and the support staff.